MERIT40 cooperates with BRCA2 to resolve DNA interstrand cross-links - Jiang, Qinqin (Genes Dev, 2015)
MERIT40 is an essential component of the RAP80 ubiquitin recognition complex that targets BRCA1 to DNA damage sites. Although this complex is required for BRCA1 foci formation, its physiologic role in DNA repair has remained enigmatic, as has its relationship to canonical DNA repair mechanisms. Surprisingly, we found that Merit40(−/−) mice displayed marked hypersensitivity to DNA interstrand cross-links (ICLs) but not whole-body irradiation. MERIT40 was rapidly recruited to ICL lesions prior to FANCD2, and Merit40-null cells exhibited delayed ICL unhooking coupled with reduced end resection and homologous recombination at ICL damage. Interestingly, Merit40 mutation exacerbated ICL-induced chromosome instability in the context of concomitant Brca2 deficiency but not in conjunction with Fancd2 mutation. These findings implicate MERIT40 in the earliest stages of ICL repair and define specific functional interactions between RAP80 complex-dependent ubiquitin recognition and the Fanconi anemia (FA)–BRCA ICL repair network.